Marketing 0.0 dan Ballerina Matrix: Model Keseimbangan Dinamis Operasional Organisasi menuju Ketidaktergantian di Era Vuca dan Kecerdasan Buatan - Sani Gazali (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study explores Marketing 0.0 and the Ballerina Matrix, a dynamic strategic framework designed to help organizations achieve irreplaceability a state where an organization is so vital to its ecosystem that it cannot be substituted within the VUCA and AI era. Moving beyond the attention economy, Marketing 0.0 shifts the focus toward creating genuine value and systemic trust. Unlike static models, the Ballerina Matrix functions as a dynamic equilibrium system mapping four operational forces: Inner Outer and Felt Measure. At its core lies the organization’s "gravity" (Qolbu, Xin, or Kokoro), which acts as a stabilizer amid environmental shifts. Through a systematic literature review and comparative analysis of industry leaders like TSMC, NVIDIA, and Patagonia, the study finds that organizational excellence is not found in optimizing one dimension, but in maintaining balance. Organizations that overemphasize the "Outer" dimension risk lacking substance, while those focusing solely on "Measure" lack meaning. The study concludes that this dynamic balance is essential for long-term resilience, relevance, and trust.